Adaptive control of nonlinear uncertain active suspension systems with prescribed performance. (January 2015) - Huang, Yingbo; Na, Jing; Wu, Xing; Liu, Xiaoqin; Guo, Yu
Abstract: This paper proposes adaptive control designs for vehicle active suspension systems with unknown nonlinear dynamics (e.g., nonlinear spring and piece-wise linear damper dynamics). An adaptive control is first proposed to stabilize the vertical vehicle displacement and thus to improve the ride comfort and to guarantee other suspension requirements (e.g., road holding and suspension space limitation) concerning the vehicle safety and mechanical constraints. An augmented neural network is developed to online compensate for the unknown nonlinearities, and a novel adaptive law is developed to estimate both NN weights and uncertain model parameters (e.g., sprung mass), where the parameter estimation error is used as a leakage term superimposed on the classical adaptations. To further improve the control performance and simplify the parameter tuning, a prescribed performance function (PPF) characterizing the error convergence rate, maximum overshoot and steady-state error is used to propose another adaptive control. The stability for the closed-loop system is proved and particular performance requirements are analyzed. Simulations are included to illustrate the effectiveness of the proposed control schemes. Highlights: Two adaptive controls are proposed for vehicle active suspension systems with unknown nonlinear dynamics. A novel adaptive law is proposed so that precise estimation of unknown parameters is achieved. A prescribed performance function (PPF) is used to address the transient and steady-state suspension performance. The performance requirement on ride comfort, road holding and mechanical limitation are all guaranteed.